2023
DOI: 10.1149/1945-7111/acb8dd
|View full text |Cite
|
Sign up to set email alerts
|

Use of Mixed Methanesulfonic Acid/Sulfuric Acid as Positive Supporting Electrolyte in Zn-Ce Redox Flow Batter

Abstract: The effect of different positive supporting electrolytes on the performance of a bench-scale Zn-Ce redox flow battery (RFB) has been studied. The effectiveness of mixed methanesulfonic/sulfuric acid, mixed methanesulfonic/nitric acid, and pure methanesulfonic acid has been assessed and compared on the basis of the cyclic voltammetric response for the Ce(III)/Ce(IV) redox couple and galvanic charge-discharge of a bench-scale Zn-Ce RFB. The Ce(III)/Ce(IV) reaction exhibits faster kinetics and the RFB exhibits hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…As shown in Figure 1A, the Zn(II) concentration in the negative electrolyte decreases steadily from 1.5 to 0.96 mol/L by the end of 30 cycles, while it increases from 0 to ~0.66 mol/L over the same period in the positive electrolyte. This change is accompanied by a rise of the H + concentration in the negative electrolyte from 1.0 mol/L to ~2.7 mol/L due to transfer from the positive side (Figure 1B), similar to that reported previously [27]. Since these determinations are made at the end of discharge, the Zn(II) concentration measured in the negative electrolyte should ideally remain at 1.5 mol/L from cycle to cycle if no metal is lost from this side of the cell.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…As shown in Figure 1A, the Zn(II) concentration in the negative electrolyte decreases steadily from 1.5 to 0.96 mol/L by the end of 30 cycles, while it increases from 0 to ~0.66 mol/L over the same period in the positive electrolyte. This change is accompanied by a rise of the H + concentration in the negative electrolyte from 1.0 mol/L to ~2.7 mol/L due to transfer from the positive side (Figure 1B), similar to that reported previously [27]. Since these determinations are made at the end of discharge, the Zn(II) concentration measured in the negative electrolyte should ideally remain at 1.5 mol/L from cycle to cycle if no metal is lost from this side of the cell.…”
Section: Resultssupporting
confidence: 89%
“…It is not surprising then that these trends can ultimately lead to the complete failure of the battery [16]. in 2/0.5 MA (data obtained in the absence of Zn(II) was originally reported in our previous study [27]) is shown in Figure 3A. The higher coulombic efficiency achieved by switching from the 4 mol/L MSA to 2/0.5 MA supporting electrolyte can be attributed to the reduction in H + 14 concentration difference between the two sides of the membrane, leading to less crossover of H + to the negative electrolyte and lower extent of the irreversible hydrogen evolution side reaction during charge.…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“… 171 The use of elevated temperatures is required to boost the sluggish kinetics of the cerium( iv )/cerium( iii ) redox couple. 172 On the other hand, from the point of view of the critically of the materials, the zinc-cerium RFB is advantageous. Zinc and cerium are both earth-abundant elements.…”
Section: Redox Flow Battery Electrolytesmentioning
confidence: 99%